Bifurcation of rupture path by linear and cubic damping force - Dennis, L.C.C. (American Institute of Physics Inc., 2014)
Bifurcation of rupture path is studied for the effect of linear and cubic damping. Momentum equation with Rayleigh factor was transformed into ordinary differential form. Bernoulli differential equation was obtained and solved by the separation of variables. Analytical or exact solutions yielded the bifurcation was visible at imaginary part when the wave was non dispersive. For the dispersive wave, bifurcation of rupture path was invisible. Â© 2014 AIP Publishing LLC.